2014
DOI: 10.1159/000370252
|View full text |Cite
|
Sign up to set email alerts
|

Yes-Associated Protein Expression is a Predictive Marker for Recurrence of Hepatocellular Carcinoma after Liver Transplantation

Abstract: Purpose: To explore the expression of Yes-associated protein (YAP) in hepatocellular carcinoma (HCC) patients, and assess its prognostic value to recurrence of HCC after liver transplantation (LT). Methods: Collected data of 105 consecutive patients undergoing LT for HCC were analyzed retrospectively. The immunohistochemistry was used to detect the expression of YAP, Mst1, Lats1/2, pYAP, pLats1/2 and pMst1/2 in tumor tissues. Contingency table and χ2-test were used to investigate the correlation bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 37 publications
2
25
0
Order By: Relevance
“…Nevertheless, we did observe a similar trend in the tumor progression of pT1 stage HCC patients. These results are consistent with previous studies reporting on the prognostic value of activated YAP1 in CCAs and HCCs [28, 29]…”
Section: Discussionsupporting
confidence: 94%
“…Nevertheless, we did observe a similar trend in the tumor progression of pT1 stage HCC patients. These results are consistent with previous studies reporting on the prognostic value of activated YAP1 in CCAs and HCCs [28, 29]…”
Section: Discussionsupporting
confidence: 94%
“…YAP has been proven to be upregulated in various types of cancer, including HCC (11,25). In the present study, it was revealed that overexpression of YAP in HCC is associated with the tumor differentiation.…”
Section: Discussionsupporting
confidence: 48%
“…Therefore, the plasma GPx3, which is negatively associated with inflammatory environment in the liver graft, was identified to be correlated with prognosis post-transplantation. Recently, a series of novel markers for HCC recurrence after liver transplantation were identified, such as CD147 28, HOTAIR 29, YAP 30 and MALAT1 31. However, they may not possess the therapeutic effect to prevent tumor recurrence.…”
Section: Discussionmentioning
confidence: 99%